Analysis of performance appraisal system with 360 degree feedback method in PT. PERTAMINA RU IV (PERSERO) Cilacap - Dina Prasetyaningrum; Yudi Agus Setiawan (The Management Journal of Binaniaga, 2020)
The 360 degree feedback method is one of the performance appraisal methods which implementation takes an assessment of the parties around the employee being assessed. The 360 degree feedback method performance appraisal system conducted at PT. Pertamina RU IV (Persero) Cilacap aims to determine the implementation of the performance appraisal system using the 360 degree feedback method, determine employee performance with what variables are used in performance appraisal, and obtain performance optimization. The research method used in this research uses qualitative methods with a quantitative approach. The 360 degree feedback method is used to find data from respondents, namely from superiors, colleagues, themselves and subordinates. Based on the research that had been done, it had succeeded in determining the best workers from each discipline and position based on the calculation of variables and indicators used. The 360 degree feedback performance assessment can help the company appropriately to provide rewards for workers with the highest percentage and provide punishment for workers with lowest percentage. The calculation of these variables and indicators helps the company to find the right solution in an effort to optimize the performance of its employees.Keywords: performance, performance appraisal, 360 degree feedback method